Whip-Lock Stitch Is Biomechanically Superior to Whipstitch for Semitendinosus Tendons - Miguel A. Diaz, M.S; Eric A. Branch, M.D; Jacob G. Dunn, D.O; Anthony Brothers, M.D; Steve E. Jordan, M.D (Elsevier, 2024)
Purpose: To assess the biomechanical performance of different stitching methods using a suturing device by comparing the elongation, stiffness, failure load, and time to stitch completion in cadaveric semitendinosus tendons (STs) and quadriceps tendons (QTs). Methods: A total of 24 STs and 16 QTs were harvested from cadaveric knee specimens (N = 40). Samples were randomly divided into 2 groups: whipstitch (WS) and whip-lock (WL) stitch. Both tendon ends were clamped to a graft preparation stand, and a 2-part needle was used to place 5 stitches, each 0.5 cm apart. Stitching time was recorded. Samples were preconditioned and then underwent cyclic loading from 50 to 200 N at 1 Hz for 500 cycles, followed by load-to-failure testing at 20 mm/min. Stiffness (in newtons per millimeter), ultimate failure load (in newtons), peak-to-peak displacement (in millimeters), elongation (in millimeters), and failure displacement (in millimeters) were recorded. Results: Completion of the WS was significantly faster than the WL stitch in the ST (P < .001) and QT (P = .004). For the ST, the WL stitch exhibited higher ultimate failure loads and construct stiffness than the WS. Regarding the QT, the WL stitch showed higher stiffness and displacement than the WS; however, the ultimate failure load was higher for the WS in the QT. The ultimate failure load in the QT was higher than that in the ST for both stitches. In the ST, only 25% of WSs and 100% of WL stitches failed due to suture breakage. In the QT, suture breakage led to the failure of 100% of both the WL stitches and WSs. Conclusions: In the ST, the WL stitch resulted in improved biomechanical performance through higher ultimate load and fewer failures from tissue damage compared with the WS. In the QT, both the WS and the WL stitch showed similar biomechanical performance with ultimate failure loads above established clinical failure thresholds. Clinical Relevance: Various types of ligament and tendon injuries require suturing to enable repair or reconstruction. The success of ligament or tendon surgery often relies on soft-tissue quality. It is important to investigate the biomechanical properties of stitching techniques that help preserve soft-tissue quality as a step to determining their clinical suitability.